1980
DOI: 10.1176/appi.psychotherapy.1980.34.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Supervision and Self-Esteem in Psychiatric Teaching

Abstract: This paper focuses on the supervisory tasks of empathizing with the student so as to appreciate the student's observations and transferences. It is shown that empathy becomes more difficult to achieve in the training of the foreign graduate whose situation is used as a paradigm for understanding of the teaching tasks. A prominent issue in this paper is the elaboration of the transference needs of the student.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Empathy's importance in supervision cannot be overstated (Ladany et al, 2016): It enables the supervisor to build and strengthen the relational bond (see Bond box, Figure 1) through developmental understanding and responsiveness (Friedlander, 2012(Friedlander, , 2015. Empathy is indeed a, if not the, vital particular of effective supervision (Muslin & Val, 1980), accordingly critical to relationship development in the CSRM.…”
Section: Connectionmentioning
confidence: 99%
“…Empathy's importance in supervision cannot be overstated (Ladany et al, 2016): It enables the supervisor to build and strengthen the relational bond (see Bond box, Figure 1) through developmental understanding and responsiveness (Friedlander, 2012(Friedlander, , 2015. Empathy is indeed a, if not the, vital particular of effective supervision (Muslin & Val, 1980), accordingly critical to relationship development in the CSRM.…”
Section: Connectionmentioning
confidence: 99%
“…Much of the writing in this area assumed, as did Maddison [7] that the relationship between the trainee and supervisor was the key to successful supervision. In the American writing on psychotherapy supervision, which informed current concepts of general clinical supervision, the relationship was conceptualized in psychoanalytic terms, with reference to transference and counter transference, Oedipal issues, narcissistic needs, and inner conflicts of the participants [36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…In identifying articles for review, the following steps were taken: (a) database searches using the PEP Web, PsycInfo, MedLine, Education Research Complete, and Google Scholar were conducted; (b) reference sections of all identified articles were reviewed for missed publications; and (c) varied psychoanalytic journals were manually examined for any recently released publications. Because the first self psychology/supervision article appears to have been published in 1980 (Muslin & Val, 1980), the combined database searches spanned from then up through August, 2014. Key words inputted for the search were “supervision” and “self psychology.” Based on the three preceding steps, the first search yielded a body of 25 self psychology supervision articles (Brightman, 1984–1985; Elson, 1989; Fosshage, 1997; Fuqua, 1994, 2006; Galatzer-Levy, 1988; Kindler, 1998; Koenig, 1997; Martino, 2001; Meyers, 1988; Muslin & Val, 1980, 1989; Pajak, 1981, 1986; Reams, 1994; Ricci, 1995; Siegel & Topel, 2000; Sloane, 1986; Teicholz, 2007; Watkins, 2013e; Wolf, 1989, 1995; Wool, 1989; Yerushalmi, 1994, 1999).…”
Section: How Is Supervisee Learning Understood? a Self Psychology Viewmentioning
confidence: 99%
“…Because the first self psychology/supervision article appears to have been published in 1980 (Muslin & Val, 1980), the combined database searches spanned from then up through August, 2014. Key words inputted for the search were “supervision” and “self psychology.” Based on the three preceding steps, the first search yielded a body of 25 self psychology supervision articles (Brightman, 1984–1985; Elson, 1989; Fosshage, 1997; Fuqua, 1994, 2006; Galatzer-Levy, 1988; Kindler, 1998; Koenig, 1997; Martino, 2001; Meyers, 1988; Muslin & Val, 1980, 1989; Pajak, 1981, 1986; Reams, 1994; Ricci, 1995; Siegel & Topel, 2000; Sloane, 1986; Teicholz, 2007; Watkins, 2013e; Wolf, 1989, 1995; Wool, 1989; Yerushalmi, 1994, 1999). Based on my second search, six additional publications were identified (Berger, 1987, Chapter 14; Gardner, 1995; Mitchell, 2009; Mordecai, 1991; Nye, 2002; Rosbrow, 1997).…”
Section: How Is Supervisee Learning Understood? a Self Psychology Viewmentioning
confidence: 99%